2022
DOI: 10.1007/s10389-022-01733-z
|View full text |Cite
|
Sign up to set email alerts
|

Mass media pressure on psychological and healthy well-being. An explanatory model as a function of physical activity

Abstract: Objectives The present research aims to identify and establish the relationships between media pressure, psychological well-being, age, physical activity and adherence to the Mediterranean diet. This objective is broken down into (a) developing an explanatory model of media pressure, psychological well-being, age, physical activity and adherence to the Mediterranean diet and (b) testing the structural model by means of a multi-group analysis according to physical activity level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…Continuing with structural equation modelling, negative relationships were observed between psychological well-being and media pressure. In view of these results, Marfil-Carmona et al (2021) and González-Valero et al (2022) argue that the media can play a negative role on psychological well-being. In this case, during COVID-19 confinement, it was found that continuous exposure to news related to the pandemic had a negative impact on people’s mental health ( Eden et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Continuing with structural equation modelling, negative relationships were observed between psychological well-being and media pressure. In view of these results, Marfil-Carmona et al (2021) and González-Valero et al (2022) argue that the media can play a negative role on psychological well-being. In this case, during COVID-19 confinement, it was found that continuous exposure to news related to the pandemic had a negative impact on people’s mental health ( Eden et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Social networks have been revealed to be the main vehicle for transmitting ideals related to body image [ 13 ]. The achievement of the type of body image transmitted via the media has also been shown to sometimes provide a motivation for young people to engage in sport [ 14 ]. This can lead to obsessive engagement [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The achievement of the type of body image transmitted via the media has also been shown to sometimes provide a motivation for young people to engage in sport [ 14 ]. This can lead to obsessive engagement [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations